Kajian Perbandingan di antara Ujian H-Ometer dan Ujian Brazilian - Omar, Husaini (Universiti Putra Malaysia Press, 2002)
The comparison study is carried out between H-O meter test and Brazilian test. In this study, the artificial weak rock or make-up sample is used. This is because the contents of the materials are known, the sample can be controlled and it is assumed to be isotropic and homogenous. Both of the test results are reported and discussed. The tensile strength from the H-O meter, a ho test shows slightly higher than the Brazilian test, a b. It is equal to 1.043 times of the tensile strength from the Brazilian test. Based on the correlation, the H-O meter test shows a good agreement with the Brazilian test.